STRATEGI PENGEMBANGAN FASILITAS UMUM PASAR WISATA KOTA BUKITTINGGI - Suwita, Suwita; Chair, Ira Meirina; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2017)
This research aims to determine the development strategy of public facilities that have internal indicators are strengths and weaknesses, and than external indicators are opportunities and threats. This research was descriptive research with qualitative data. Technique of data collected by using interviews, observation and documentation. Determination of informants using Purposive Sampling technique, and Snow-Ball Sampling. Strategy for the development of public facilities Tourism Market are strategic location and the availability of land can be utilized to build unavailable facilities such as waiting areas and children's playgrounds, improving parking systems such as building special parking spaces for the two-wheeled and four-wheeled vehicles, As well as making programs such as "Parking Discount Cards" so that visitors prioritize using parking services at the Tourism Market location compared to using other parking services, maintaining clean water quality and cleanliness of public toilet with routine daily check and repair facilities completeness in public toilet such as lighting conditions, scoop conditions and the availability of garbage bins in the toilet, forming a member of the merchant board of Mosque and make mutual assistance program on a regular basis while for the relevant office can do the renovation and supervision of the use of Mosque, disseminates the promotional benefits of the Market Service to the merchant so that the available stall / store can be utilized by the shopkeeper to do the promotion through the installation of the store's signboard by creating a personal brand, in addition to making shopping programs such as discount programs, Sales, and other programs that can attract visitors, the majority of visitors who come from many families can use as a target market by building a child-friendly facilities such as waiting areas and small playgrounds such as small slides and swings so it does not require land Wide and no land constriction.Keywords: strategy, development, public facilities, tourism market